2005
DOI: 10.1097/01.tp.0000184842.01686.ca
|View full text |Cite
|
Sign up to set email alerts
|

Renal Graft Survival and Calcineurin Inhibitor

Abstract: Although tacrolimus is being used with increasing frequency, analyses of the USRDS data show no net advantage in the ultimate transplantation outcome, graft survival. Given the higher acquisition price of tacrolimus compared to CsA and the similar risk of graft failure, further studies should be conducted to define those patient groups for which tacrolimus might be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Using both methods, we demonstrated the upper quartile as being by far the highest risk category, and within these categories we demonstrated threshold levels of eGFR MDRD 1yr <27 mLs/min/1.73m 2 and SCr 1yr >229 μmol/L for accelerated risk of graft failure. These are useful clinical values and serve to highlight the cohort of patients likely to require an early return to renal replacement therapy or re-transplant.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Using both methods, we demonstrated the upper quartile as being by far the highest risk category, and within these categories we demonstrated threshold levels of eGFR MDRD 1yr <27 mLs/min/1.73m 2 and SCr 1yr >229 μmol/L for accelerated risk of graft failure. These are useful clinical values and serve to highlight the cohort of patients likely to require an early return to renal replacement therapy or re-transplant.…”
Section: Discussionmentioning
confidence: 77%
“…Newer maintenance immunosuppressive regimes, featuring tacrolimus and mycophenolate mofetil, have reduced the acute rejection rate; however, their effect on long-term graft outcome is not without debate. [2][3][4][5][6][7] One-year graft survival rates in our cohort of patients have improved from 82% to 86% in the period 1986-2001. [8] Irish Renal Transplant Registry data indicate that our acute rejection rate has improved from 30% in the 1990s to less than 10% currently.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of OTRs are managed on multiple immunosuppressive agents, which generally include one calcineurin inhibitor (CSA or tacrolimus), along with an antimetabolite (azathioprine or mycophenolate) and prednisolone (39). Tacrolimus has become increasingly popular in transplant patients over recent years, largely due to studies suggesting it has a lower risk of acute rejection in comparison to CSA; however, despite this popularity, there have been no clear benefits seen in long-term rejection rates (40,41). Tacrolimus, while also acting via calcineurin inhibition, has different toxicities and a differing side effect profile; because of this, it is not the best suited CNI for every patient (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…At 3 y after transplant, the low-dose tacrolimus arm continued to have the highest graft survival rate and the least acute rejection (64). In contrast, two other retrospective studies of the United States Renal Data System data found that there was either no difference in allograft survival (65) or improved allograft survival with cyclosporine (66). These conflicting data could be explained by multiple variables in those studies, including dosing and various cyclosporine preparations.…”
Section: Cyclosporine Versus Tacrolimusmentioning
confidence: 96%